Moment of Inertia

The moment of inertia of a lamina S : x 2 + y 2 = 1 , ( 0 z h ) { S: x^2 + y^2 = 1, (0 \leq z \leq h) } of unit density about the line z = h 2 { z = \frac{h}{2} } in the x z p l a n e { xz \: plane } can be represented by π h ( h 2 a + b ) \pi \cdot h \left(\dfrac{h^2}{a} + b\right) , where gcd ( a , b ) = 1. { \gcd(a,b) = 1. }

Find: a + b { a + b } .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Steven Chase
Oct 27, 2016

I was amazed when I first learnt about the Parallel Axis Theorem , and how it could greatly simplifies calculating moment of inertia through an arbitrary axis.

Calvin Lin Staff - 4 years, 7 months ago

Log in to reply

Yeah, it's great. My general approach is either to use the PAT or represent it as a double (or triple) integral and compute it numerically.

Steven Chase - 4 years, 7 months ago
Rocco Dalto
Oct 27, 2016

Two points on line z = h 2 {\bf z = \frac{h}{2} } in the x z p l a n e {\bf xz \: plane } are:

A : ( 0 , 0 , h 2 ) a n d B : ( 1 , 0 , h 2 ) {\bf A:(0,0,\frac{h}{2}) \: and \: B:(1,0,\frac{h}{2}) \implies }

Line A B i s : x = t , y = 0 , z = h 2 {\bf AB \: is: x = t, y = 0, z = \frac{h}{2} } , where the direction numbers of line A B a r e u = i + 0 j + 0 k {\bf AB \:\ are \: \vec{u} = \vec{i} + 0\vec{j} + 0\vec{k} }

Let P : ( x , y , z ) {\bf P:(x,y,z) } be a point not on line A B {\bf AB } and v = x i + y j + ( z h 2 ) k {\bf \vec{v} = x\vec{i} + y\vec{j} + (z - \frac{h}{2})\vec{k} } be vector from point A t o P . {\bf A \: to \: P. }

The distance d {\bf d } from point P {\bf P } to line A B {\bf AB } is: d = u X v u {\bf d = \frac{|\vec{u} X \vec{v}|}{|\vec{u}|} }

u X v = 0 i + ( z h 2 ) j + y k a n d u 2 = 1 {\bf \vec{u} X \vec{v} = 0\vec{i} + -(z - \frac{h}{2})\vec{j} + y\vec{k} \: and \: |\vec{u}|^2 = 1 \implies}

d 2 = ( z h 2 ) 2 + y 2 {\bf d^2 = (z - \frac{h}{2})^2 + y^2 }

for x 2 + y 2 = 1 , ( 0 < = z < = h ) r ( u , z ) = c o s ( u ) i + s i n ( u ) j + z k {\bf x^2 + y^2 = 1, (0 <= z <= h) \implies \vec{r}(u,z) = cos(u)\vec{i} + sin(u)\vec{j} + z\vec{k} } where ( 0 < = u < = 2 π ) {\bf (0 <= u <= 2\pi) } and ( 0 < = z < = h ) {\bf (0 <= z <= h) \implies }

r u = s i n ( u ) i + c o s ( u ) j + 0 k , {\bf \vec{r_{u}} = -sin(u)\vec{i} + cos(u)\vec{j} + 0\vec{k}, } and r z = 0 i + 0 j + k {\bf \vec{r_{z}} = 0\vec{i} + 0\vec{j} + \vec{k} \implies }

r u X r z = c o s ( u ) i + s i n ( u ) j + 0 k r u X r z = 1 {\bf \vec{r_{u}} X \vec{r_{z}} = cos(u)\vec{i} + sin(u)\vec{j} + 0\vec{k} \implies |\vec{r_{u}} X \vec{r_{z}}| = 1}

d A = r u X r z d u d z = d u d z {\bf \implies dA = |\vec{r_{u}} X \vec{r_{z}}| du \: dz = du \: dz }

and, d 2 = ( z h 2 ) 2 + y 2 = z 2 h z + h 2 4 + s i n 2 ( u ) {\bf d^2 = (z - \frac{h}{2})^2 + y^2 = z^2 - hz + \frac{h^2}{4} + sin^2(u) \implies }

S d 2 d A = 0 h 0 2 π ( z 2 h z + h 2 4 + s i n 2 ( u ) ) d u d z = {\bf \int \int_{S} d^2 dA = \int_{0}^{h} \int_{0}^{2\pi} (z^2 - hz + \frac{h^2}{4} + sin^2(u)) du \: dz = }

0 h ( ( z 2 h z + h 2 4 ) u + 1 2 ( u 1 2 s i n ( 2 u ) ) ) 0 2 π d z = {\bf \int_{0}^{h} ( (z^2 - hz + \frac{h^2}{4}) * u + \frac{1}{2} * (u - \frac{1}{2} sin(2u)) )|_{0}^{2\pi} dz= }

2 π 0 h z 2 h z + h 2 4 + 1 2 d z = 2 π ( z 3 3 h z 2 2 + h 2 z 4 + z 2 ) 0 h = 2 π ( h 3 12 + h 2 ) {\bf 2\pi * \int_{0}^{h} z^2 - hz + \frac{h^2}{4} + \frac{1}{2} \: dz = 2\pi * (\frac{z^3}{3} - \frac{h * z^2}{2} + \frac{h^2 * z}{4} + \frac{z}{2} )|_{0}^{h} = 2\pi (\frac{h^3}{12} + \frac{h}{2} ) }

= π h 6 ( h 2 + 6 ) = π h ( h 2 6 + 1 ) = π h ( h 2 a + b ) a + b = 7. {\bf = \frac{\pi * h}{6} * (h^2 + 6) = \pi * h (\frac{h^2}{6} + 1) = \pi * h (\frac{h^2}{a} + b ) \implies a + b = 7. }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...